Direct Parent Engagement to Improve Fundamental Movement Skills in Children: A Systematic Review - Robert J. Flynn; Andy Pringle; Clare M. P. Roscoe (MDPI AG, 2023)
Fundamental movement skills (FMS) are basic movements in children that represent the building blocks for more complex motor skill development and act as a prerequisite for enduring sport and physical activity (PA) engagement and positive health-related behaviours. The FMS proficiency is currently inadequate worldwide, and consequently there are alarming levels of inactivity and childhood obesity. However, parents are role models to their children and possess the power to influence their PA behaviour. This review investigated if parent-focused interventions could improve FMS in 2-7-year-old children and evaluated which setting and method of parent engagement was most impactful. Keyword searches were conducted via Scopus, Web of Science, SPORTDiscus, PubMed, Science Direct, and Google Scholar. Only nine articles met the inclusion criteria. No research originated from the United Kingdom, highlighting the urgent need for further FMS interventions involving parents. The FMS improved in all nine studies, with significant changes in seven of the articles (p < 0.05). Parent-child co-activity, the education and empowerment of parents, and the provision of clear FMS guidance, messaging, and structure can positively influence children's FMS. Recently, smartphone apps have increased the feasibility and accessibility of FMS practice at home and may be integral to future interventions. Further research with direct parental involvement is clearly warranted.